A calculus problem by Md Zuhair

Calculus Level 3

If lim x 0 1 cos 2 x 1 cos 3 x = a b \displaystyle \lim_{x\to 0} \dfrac{1- \cos 2x}{ 1- \cos3x} = \dfrac{a}{b} , where a a and b b are coprime positive integers, find a + b a+b .


The answer is 13.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Feb 21, 2017

Solution 1: by Maclaurin series

L = lim x 0 1 cos 2 x 1 cos 3 x By Maclaurin series expansion = lim x 0 1 ( 1 2 2 x 2 2 ! + 2 4 x 4 4 ! . . . ) 1 ( 1 3 2 x 2 2 ! + 3 4 x 4 4 ! . . . ) = lim x 0 2 2 x 2 2 ! 2 4 x 4 4 ! + 2 6 x 6 6 ! . . . 3 2 x 2 2 ! 3 4 x 4 4 ! + 3 6 x 6 6 ! . . . Divide up and down by x 2 = lim x 0 2 2 2 ! 2 4 x 2 4 ! + 2 6 x 4 6 ! . . . 3 2 2 ! 3 4 x 2 4 ! + 3 6 x 4 6 ! . . . = 2 2 3 2 = 4 9 \begin{aligned} L & = \lim_{x \to 0} \frac {1- \color{#3D99F6} \cos 2x}{1- \color{#3D99F6} \cos 3x} & \small \color{#3D99F6} \text{By Maclaurin series expansion} \\ & = \lim_{x \to 0} \frac {1-\left(1 - \frac {2^2x^2}{2!} + \frac {2^4x^4}{4!} - ...\right)}{1-\left(1 - \frac {3^2x^2}{2!} + \frac {3^4x^4}{4!} - ...\right)} \\ & = \lim_{x \to 0} \frac {\frac {2^2x^2}{2!} - \frac {2^4x^4}{4!} + \frac {2^6x^6}{6!} - ...}{\frac {3^2x^2}{2!} - \frac {3^4x^4}{4!} + \frac {3^6x^6}{6!} -...} & \small \color{#3D99F6} \text{Divide up and down by }x^2 \\ & = \lim_{x \to 0} \frac {\frac {2^2}{2!} - \frac {2^4x^2}{4!} + \frac {2^6x^4}{6!} - ...}{\frac {3^2}{2!} - \frac {3^4x^2}{4!} + \frac {3^6x^4}{6!} -...} \\ & = \frac {2^2}{3^2} = \frac 49 \end{aligned}

a + b = 4 + 9 = 13 \implies a + b = 4+9 = \boxed{13}


Solution 2: by L'Hôpital's rule

L = lim x 0 1 cos 2 x 1 cos 3 x A 0/0 case, L’H o ˆ pital’s rule applies. = lim x 0 2 sin 2 x 3 sin 3 x A 0/0 case and apply L’H o ˆ pital’s rule again. = lim x 0 4 cos 2 x 9 cos 3 x Differentiate up and down w.r.t x = 4 9 \begin{aligned} L & = \lim_{x \to 0} \frac {1- \cos 2x}{1- \cos 3x} & \small \color{#3D99F6} \text{A 0/0 case, L'Hôpital's rule applies.} \\ & = \lim_{x \to 0} \frac {2 \sin 2x}{3 \sin 3x} & \small \color{#3D99F6} \text{A 0/0 case and apply L'Hôpital's rule again.} \\ & = \lim_{x \to 0} \frac {-4 \cos 2x}{-9 \cos 3x} & \small \color{#3D99F6} \text{Differentiate up and down w.r.t }x \\ & = \frac 49 \end{aligned}

a + b = 4 + 9 = 13 \implies a + b = 4+9 = \boxed{13}

Why should i try Maclaurin one? I think easier is L'Hospital for this sum. But anyways, Your solutions are always awesome with black and blue text.

Md Zuhair - 4 years, 3 months ago

@Chew-Seong Cheong sir, Can i expect a solution from you for this question, Inequality Masterpeice

Md Zuhair - 4 years, 3 months ago
Mohd Aasif
Feb 20, 2017

We use L-Hopital to solve this type of problem {(-)(sin2x) 2}/{(-)(sin3x) 3}=4/9 a=4 b=9 so a+b=13

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...